Adaptation of eTwinning in higher education: Its impact on English teaching: Adaptación de eTwinning en educación superior: Su impacto en la enseñanza del inglés - Basantes, María Cristina (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2025)
This study explores the potential of classroom twinning and virtual exchange programs, particularly through eTwinning (inspired by an initiative of the European Commission's eLearning Program in 2005), as a strategy to enhance English proficiency in countries with low EF EPI rankings. By facilitating digital collaboration between EFL learners and native English speakers, these initiatives aim to improve language acquisition, intercultural competence, and student motivation. The literature review synthesizes recent research on telecollaboration and blended learning models, emphasizing their role in foreign language education. A systematic literature search was conducted in indexed databases, focusing on studies published since 2020. Inclusion criteria prioritized research examining classroom twinning projects, digital collaboration, and their impact on EFL learners' language proficiency. Excluded were studies unrelated to language acquisition or intercultural exchange. The findings highlight the positive effects of virtual interactions on linguistic skills, digital literacy, and cultural awareness, while also identifying challenges related to time zone differences, curriculum misalignment, and unequal technological access. The study proposes a three-year phased implementation of eTwinning in universities, beginning with pilot programs, faculty training, and technological integration, followed by institutional adoption. Future research should address the impact of technological disparities on student participation, the role of teacher training in virtual exchanges, and strategies to enhance oral proficiency in digital environments. The findings provide practical recommendations for integrating digital collaboration into EFL education, contributing to innovative pedagogical practices in foreign language learning.